2011
DOI: 10.4100/jhse.2011.61.15
|View full text |Cite
|
Sign up to set email alerts
|

Fitness test profiles in children aged 8-12 years old in Granada (Spain)

Abstract: Fitness test profiles in children aged 8-12 years old in Granada (Spain). J. Hum. Sport Exerc. Vol. 6, No. 1, pp. 135-145, 2011. The aim of this study was to determine the effects of physical education in body composition and health-related fitness among boys and girls aged 8 to 12 years old in Granada (Spain) in a longitudinal, randomized study of 5 months. 106 children (49 boys and 57 girls) between 8 and 12 years old completed the study. They were healthy students of the public schools and no history of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…Health-related fitness includes, besides others, aerobic endurance, muscular strength, and flexibility (Hands et al, 2009). On this, most studies on physical fitness have focused specially on aerobic capacity neglecting, among for instance, neuromotor fitness based on muscular strength (Cepero et al, 2011). Some studies reported positive associations between physical activity in children and adolescents with performance on tests of muscular strength and muscular endurance (Lennox et al 2008; Martínez-Gómez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related fitness includes, besides others, aerobic endurance, muscular strength, and flexibility (Hands et al, 2009). On this, most studies on physical fitness have focused specially on aerobic capacity neglecting, among for instance, neuromotor fitness based on muscular strength (Cepero et al, 2011). Some studies reported positive associations between physical activity in children and adolescents with performance on tests of muscular strength and muscular endurance (Lennox et al 2008; Martínez-Gómez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there are few studies that link somatype with muscular strength in young people, with the exception of the recent studies by Jakšić and Cvetkovic (2009) and Shukla et al (2009) relating this exclusively to the standing broad jump and curl-ups. Currently, efforts to promote physical fitness levels in the young ought to be a priority (Cepero et al, 2011), but clearly these cannot exceed the limits imposed by genotype, i.e., the manifestation of genetic determinism; just as important as the dimensional values are their relative degrees of presence, observed from the morpho-constitutional perspective (Malina and Bouchard, 1991). We can define the morphological typology as a complex entity that describes the overall configuration of the body, as opposed to individual anatomical characteristics (Malina and Bouchard, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…But health-related fitness showed differences by gender only in slalom (p<0.05). The results of body composition and health-related fitness revealed that the physical activity at school is not sufficient to support an ideal level of health-related fitness [18]. Therefore, we should treat seriously the problem in new school interventions in order to achievement better effects of education.Well recognized gender differences aerobic power [19], muscle strength [20] and obesity [21] in primary school children.…”
Section: Discussionmentioning
confidence: 99%
“…Achievements of girls were consistently lower than boys', perhaps reflecting their earlier maturation. The aim of the Spanish study was to determine the effects of Physical Education on body composition and health-related fitness (EUROFIT) among boys and girls aged 8 to 12 years old [18]. Subjects were tested at baseline and at week 20.…”
Section: Discussionmentioning
confidence: 99%
“…The classic sit-and-reach test (also called traditional or standard sit-and-reach), originally designed by Wells & Dillon (1952), is probably the most widely used lineal test of flexibility in exercise science laboratories, physical education classes, and commercial fitness centres (Cepero et al, 2011;Holt et al, 1999;Mirzaei et al, 2011). Two years later, Kraus & Hirschland (1954) designed the toe-touch (TT) test in which the individuals were assessed standing instead of sitting on the floor like in the classic sit-and-reach test.…”
Section: Introductionmentioning
confidence: 99%